BALINESE PLANNING PHILOSOPHY: IMPLEMENTATION IN DENPASAR CITY PLAN - K.A.P. Wijaya; Hanny Wahidin Wiranegara (International Journal on Livable Space, 2020)
ABSTRACT Tri Hita Karana, Tri Mandala, and Sanga Mandala are the Balinese spatial planning philosophies. Core values in Tri Hita Karana are balanced and harmony among parahyangan, palemahan, and pawongan. Denpasar city plan was stated formally based on Tri Hita Karana. Application of this concept was revealed into Tri Mandala and Sanga Mandala which producing nine zones. If these philosophy implemented fully then the land allotment in the spatial plan follow the rules and there is no problem of disharmony between the elements of Tri Hita Karana. The purpose of this study is to identify deviations in the application of traditional Balinese spatial concepts in the Denpasar city plan and proposed prevention of the emergence of problems in its implementation. To find deviations between the Tri Hita Karana concept and the city spatial plan, an overlapping analysis was conducted between the Sanga Mandala zoning and the Denpasar city spatial plan. The results show that there have been deviations in various zones. To prevent the emergence of problems due to deviations, implementation needs to be supported by zoning regulations and other supporting regulations. Keywords: tri hita karana, city spatial plan